A proteção dos credores de empresas em crise no Brasil: uma investigação sobre o dever de requerer autofalência e institutos afins no direito brasileiro - Marcus de Freitas Gouvêa (2022)
Many jurisdictions have been passing legal features on facilitating the rescue of distressed firms and, at the same time, rules on creditors’ protection when the firm approaches financial difficulties, according the recommendation of international organisms, as the IMF and the World Bank. Those mechanisms, beyond providing a balanced protection to creditors and debtors, are moved by two reasons. First, the expectation that the sooner the financial problems are detected and the corrective measures taken, the lesser are the chances that the firm becomes insolvent, and the smaller the costs and losses a possible liquidation may cause to creditors and to the society. Second, despite the conception that directors should prioritize shareholders’ interests, they cannot do it on creditors, suppliers and employees’ expenses. The creditors’ protection systems are classified by the literature in two groups, one that imposes the director the obligation to apply for the firm’s liquidation when it becomes insolvent, and another one more flexible, which imposes the directors the duty to consider the creditors’ interests when the firm approaches the insolvency, but not necessarily requires the firm’s liquidation. Despite their different mechanisms, the function of these legal features is to incentivize the directors to constantly and effectively monitor the firm’s financial condition, so that they are able to take rational decisions in benefit of the shareholders but also to other stockholders, as the creditors. Considering that Brazil does not explicitly adopts such legal features, as recommended by international organisms, this research intends to investigate whether Brazilian law contains any legal features that may provide to creditors a similar protection from debtors in financial crises as other legal features do. The research concludes the Brazilian law contains rules that are able to provide some protection to creditors, by imposing liabilities, based on the tort law, on directors who make decisions involving the hasty liquidation of firm’s assets, the use of ruinous means to make payment, unjustified expenses, and the unjustified decapitalization of the firm. Nonetheless, there are little evidence of those rules’ enforcement, possibly due to the high burden of proof to make a director responsible according to the general rules of tort law, and to the prevalence of corporate veil lifting in the case law, measure that compensate the estate, but does not present the same effects on the firm’s monitoring and on the directors’ duty of care, what suggests the possibility of some amendments in Brazilian Law.